The Public Defensory's act in promoting the right to access justice in Brazil (Research, Society and Development, 2020)
This article aims to analyze the various forms of action of the Public Defender in Brazil to promote the right of access to justice. The organization of the Public Defender and its objectives are foreseen in the Federal Constitution of 1988 and in Complementary Law No. 80 of 1994, having, with that institution, a commitment to the promotion of fundamental rights and access to justice for  hyposufficient people . The method used in the work is deductive, based on bibliographic research. The study addresses the meaning of the right of access to justice, analyzing its change over time, and subsequently verifies the role of the Public Defender in terms of promoting access to justice for people in situations of economic and social vulnerability. The function of the Public Defender involves legal assistance in the judicial as well as extrajudicial scope, and also the mission of informing people about their rights, so that they can later be exercised. The paper points out that offering legal assistance to hyposufficient groups such as women, the elderly, children, homeless people and economically disadvantaged people, the Public Defender promotes access to justice, contributing to the effectiveness of fundamental rights such as the right to health, education, housing , broad defense and contradictory, etc.